Facial middle third fractures. Experience at Dos de Mayo National Hospital, 1999 - 2009 - Avello Canisto, Francisco (2013)
Facial middle third fractures resulting from severe trauma are frequent pathology attended by Surgery Head, Neck and Maxillofacial specialists; to determine its characteristics is important for treatment. Objectives: To determine the presentation of facial middle third fractures by age, sex, causal agent. Design: Observational descriptive study. Setting: Head, Neck and Maxillofacial Surgery Service, Dos de Mayo National Hospital, Lima, Peru. Participants: Patients with facial middle third fracture. Interventions: Collection of data from medical records June 1999 through May 2009. Main outcome measures: Age, sex, causing agent and classification. Results: From 471 patients, 83% were male, 72.5% between 21 and 40 years of age; 48% resulted from traffic accidents and 25% from robberies; 83% were middle third fractures only, and 88% unilateral stroke. Conclusions: Facial middle third fractures are the most common fractures of the facial region; clinical diagnosis depends on the affected structure. Prompt treatment is necessary to prevent sequelae and complications.